ΣΧΟΛΙΑ ΣΕ ΜΙΑ ΧΑΡΤΙΝΗ ΕΙΚΟΝΑ ΤΟΥ ΒΟΡΤΟΛΙ - ΤΣΙΟΔΟΥΛΟΣ, ΣΤΕΦΑΝΟΣ (Μνήμων, 2005)
Stephanos Tsiodoulos, Comments on a copper engraving of Bortoli In this article we present a copper engraving of the Transfiguration of Christ, printed in the printing house of Bortoli, and we attempt to relate it with the village Kalota in Zagori of Epirus. In the central church of the village Kalota we found copies of the afore-mentioned copper engraving. This engraving bears under the representation the inscription: Η ΜΕΤΑΜΟΡΦΩΣΙΣ TOY ΣΩΤΗΡΟΣ ΕΙΣ ΚΑΛΟΤΑ. Also, under the decorative border that surrounds the representation, on the left side, there is the following inscription: Ε'νετίηση Παρά Άντωνίω τω Βόρτολι. The engraving should be dated before the year 1788, in which Bortoli printed his last book. It should be indicated that the central church of the village, which was built or restored in 1736, is dedicated to the Transfiguration of Christ. According to oral testimonies of the inhabitants of Kalota, in the past, every year on the 6th of August, day of the patronal feast of the church, the church wardens used to carry the collection-plare around the churchyard, in which they had placed the copper engraving of the Transfiguration of Christ. Afterwards, according to the procedure of the auction, the person who would offer the largest sum of money would become the possessor of the engraving. The above-mentioned custom stopped in the mid 1950's. The engraving used to be offered aswell to the person who would give the largest sum of money, in order to hold the cross during the procession of the Epitaph on the evening of Good Friday or in order to hold the icon of the Resurrection on the evening of Holy Saturday. Also, this engraving used to be given as a blessing by the church to the newly married couples. According to what we mentioned above, the copper engraving of the Transfiguration of Christ should be related closely with the village Kalota of Epirus.